Comparative Virulotyping of Salmonella typhi and Salmonella enteritidis - Elemfareji, O.I.; Thong, Kwai Lin (Springer Verlag, 2013)
Members of Salmonella enterica are important foodborne pathogens of significant public health concern worldwide. This study aimed to determine a range of virulence genes among typhoidal (S. typhi) and non-typhoidal (S. enteritidis) strains isolated from different geographical regions and different years. A total of 87 S. typhi and 94 S. enteritidis strains were tested for presence of 22 virulence genes by employing multiplex PCR and the genetic relatedness of these strains was further characterized by REP-PCR. In S. typhi, invA, prgH, sifA, spiC, sopB, iroN, sitC, misL, pipD, cdtB, and orfL were present in all the strains, while sopE, agfC, agfA, sefC, mgtC, and sefD were present in 98.8, 97.7, 90.8, 87.4, 87.4 and 17.2 %, of the strains, respectively. No lpfA, lpfC, pefA, spvB, or spvC was detected. Meanwhile, in S. enteritidis, 15 genes, agfA, agfC, invA, lpfA, lpfC, sefD, prgH, spiC, sopB, sopE, iroN, sitC, misL, pipD, and orfL were found in all S. enteritidis strains 100 %, followed by sifA and spvC 98.9 %, pefA, spvB and mgtC 97.8 %, and sefC 90.4 %. cdtB was absent from all S. enteritidis strains tested. REP-PCR subtyped S. typhi strains into 18 REP-types and concurred with the virulotyping results in grouping the strains, while in S. enteritidis, REP-PCR subtyped the strains into eight profiles and they were poorly distinguishable between human and animal origins. The study showed that S. typhi and S. enteritidis contain a range of virulence factors associated with pathogenesis. Virulotyping is a rapid screening method to identify and profile virulence genes in Salmonella strains, and improve an understanding of potential risk for human and animal infections.